Penamaan Selat di Kabupaten Karimun: Kajian Toponimi dan Studi Etnolinguistik: Naming of Straits in Karimun Regency: Toponimy Research and Ethnolinguistics Study - Rahmat Muhidin (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The research discusses names of straits in Karimun District relates to the history naming the straits by people around the Karimun District. This research aims to describe names of the straits in Karimun District, Riau Island Province based on toponimy and ethnolinguistics study. The method used in this research was descriptive method and literature study. The data in this research was data secundery, islands toponimy survey data, and data processing as the research design. The result shows that the naming of straits at Karimun District refers to some indicators: 1) naming region based on topography. The region given name based on shapes of the region, example: Menawang Straits, Gelam Straits, 2) naming region based on names of plants dominate or the only one and unique plant in that area. For example Seraya Straits, Asam Straits, Penarah Straits, and Lumut Straits, 3) naming of the regional based on shapes of region or regional possesion can be seen by sight, for example Panjang Straits and Kecil/Cacing Straits, 4) therefore, one of region that given named based on moment in history, the journey of human for long life or goverment history as can be seen, example Belian Straits. Based on the story there was a location as a place many people have sale and buy goods transaction and Buru Straits based on the story a king often shoots animals in the region, Bliah Straits, tongkan pecah straits named based on ship sink, Ungar Straits.Kaisar Straits, Sekajang Straits and Mandah Straits, 5) next category is naming is named the region based on name of people stay in the area, and 6) naming of region based on animal names mostly found in that area like Ketam Straits, Sekup Straits, and Kantang Straits. The straits toponim process in the region research based on shapes topography, floras, faunas, shapes and position of straits, history, and ethnicity.